Dietary polyphenols in the treatment of inflammatory bowel diseases: Polyphenols in IBD treatment - Koyuncu , Açelya Gül; Akyüz , Elvan Yılmaz (Journal of Surgery and Medicine, 2022)
Ulcerative colitis and Crohn's disease, caused by chronic inflammation in the digestive tract, are inflammatory bowel diseases and have similar symptoms. Abnormal immune responses play a pretty important role in the pathogenesis of the disease. Proinflammatory mediators trigger inflammation, stimulate cell signaling molecules, and induce disease onset. Corticosteroids, anti-tumor necrosis factor-α antibodies, and immunosuppressants are some drugs used to treat the disease. However, these drugs have some side effects. In addition, surgical methods might be used in the treatment, but these methods may have some complications. Due to the negative impact on treatment options, alternative methods for reliable, inexpensive, and effective treatment are being sought. Secondary plant compounds with an aromatic or phenolic ring structure, so-called polyphenols or phenolic compounds, may modulate cellular signaling pathways and reduce intestinal inflammation due to their antioxidant and anti-inflammatory effects. Polyphenols may be evaluated as alternative methods for inflammatory bowel disease based on these properties. This review aims to investigate the effect of some polyphenols on inflammatory bowel disease.